2011
DOI: 10.1016/j.jcrs.2011.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Six just-noticeable differences in retinal image quality in 1 line of visual acuity: Toward quantification of happy versus unhappy patients with 20/20 acuity

Abstract: Purpose To determine the number of JND's of wavefront blur necessary to induce a one line loss of best corrected visual acuity (VA). Setting Visual Optics Institute, College of Optometry, University of Houston, Houston, Texas, USA. Methods The 3mm wavefront error of a well corrected average eye was scaled to yield 9 small steps of blur quantified in units of log Visual Strehl (log VS). For each level of log VS, 10 unique three line acuity charts were convolved with the resulting point spread functions. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 20 publications
2
39
1
Order By: Relevance
“…Image quality has to change even more before a change in acuity is detected. More specifically, Ravikumar, et al 2011 demonstrated that there are on average 6 just noticeable differences in blur for every 5 letter change of logMAR acuity (one line). This “dead zone” shifts the linear regressions to the right and as a consequence, shifts the intercept of the best fitting linear regression to a slightly better acuity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Image quality has to change even more before a change in acuity is detected. More specifically, Ravikumar, et al 2011 demonstrated that there are on average 6 just noticeable differences in blur for every 5 letter change of logMAR acuity (one line). This “dead zone” shifts the linear regressions to the right and as a consequence, shifts the intercept of the best fitting linear regression to a slightly better acuity.…”
Section: Discussionmentioning
confidence: 97%
“…3 out of 4 subjects were naive to the psychophysical experiments and the design of the experiment. One subject was familiar with the approach from a previous study (Ravikumar et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3-6 More specifically, research reveals the visual Strehl (the optical Strehl ratio weighted by the neural contrast sensitivity function for interference fringes) 5 is a particularly good metric, accounting for about 80% of variance in the resulting induced change in high contrast logMAR acuity. 4,7 Despite these gains, it is not known if the naturally occurring change in optical quality over years 8-14 within an individual is as well correlated with change in acuity and the extent such measures can help identify individuals on a fast track to an acuity loss.…”
mentioning
confidence: 99%
“…26 A more recent study completed by Ravikumar et al found high correlation to distance visual acuity when taking the log of image quality metrics presented by Thibos et al; specifically logNS, logVSX, logVSMTF, and logPFSt gave R 2 Q0.86. 19,20,24 These previous studies show good correlation to distance visual acuity but still present a need for a through-focus image quality metric that takes into account the eye's natural aberrations, pupil diameter, and residual accommodative amplitude. The goal of this work was to develop a new image quality metric that is highly correlated with through-focus visual acuity and can be easily related to clinical measurements.…”
mentioning
confidence: 99%